Ibrahim Kingori Njoki v DCI Revisited - Rights of Ex-Convicts to Gainful Employment (Global Journal of Human-Social Science, 2024)
A government has the monopoly of power to punish offenders who are deemed to disrupt the good order in society This it does through a judicial process that culminates in a lawful punishment Such punishment is meant to be proportional to the wrong done Ordinarily once a person has served the punishment such a person would be deemed to have paid the debt to society However this is not the case with respect to ex-convicts and employment Many countries keep criminal records which are used to exclude ex-convicts from employment The Directorate of Criminal Investigations in Kenya has the mandate of collecting storing and disclosing criminal convictions 2 Modern developments in the protection of human rights has seen a paradigm shift towards accommodating ex-convicts in employment Different countries have adopted varied measures towards this end It is not in doubt that the age old practice of excluding ex-convicts from employment violates their right to dignity privacy and labour relations Such violation in turn endangers society through recidivism Governments the world over endeavour to ensure that a criminal is properly prepared for re-integration into society
Keywords: ex-convicts; freedom from degrading treatment; recidivism; rehabilitation; right to dignity